TEACHER ATTITUDES TOWARD CHANGE IN NATIONAL SCHOOLS AT PENINSULAR MALAYSIA - Lai, Nan Poh; Tai, Mei Kin; Omar, Abdull Kareem (International Journal of Education, Psychology and Counseling, 2021)
The study aims to identify the level of Teacher Attitudes Toward Change (TATC) among teachers in National Schools (NS) at Peninsular Malaysia. In particular, this study aims to identify TATC levels based on Cognitive, Affective, and Behavioral dimensions. This study applied a quantitative method using a survey approach. A total of 384 teachers of NS were involved in this study. The study employed descriptive statistics by obtaining the mean score and standard deviation. The findings of the study revealed that the TATC’s level as a whole was located in the quadrants of Acceptance (Mean=4.38, SD=.57). In addition, the findings of the study showed that the Cognitive (Mean=4.53, SD=.71), Affective (Mean=4.18, SD=.68), and Behavioral dimension (Mean=4.43, SD=.59) of TATC were also located at the quadrant of Acceptance. The study contributes to the teachers' understanding of the importance of their attitudes toward changes in the school. The findings of the study also provide information to the related parties to plan appropriate training programmes to enhance TATC in school.